Fundamentals of Entrepreneurship (ENT300) : Written report on identifiying a business opportinity / Debbra Juman ... [et al.] - Juman, Debra; Hannah, Hazel; Tricia, Laura; Alfred, Ordellia; Bujang, Preslyvia (2018)
In this modernazation era , car have been our need in our life and of course it plays an important role of our business which is girl car wash to help the customer with a busy life and work to have their clean vechicles for daily use. Besides we are emphasized about the need and the want of the customers. Our business are located at Kota Samarahan with about 250,000 population.Our service can reduce the burden of the customers as they did not have to go to our car wash services and it can saves their time.